The influence of ais and hr on the quality of financial reports through internal control at pt xyz - Suwono, Suwono; Setiabudhi, Hatta (Jurnal Mantik, 2025)
This study examines the influence of Accounting Information Systems (AIS) and Human Resources (HR) on the quality of financial reports through the mediating role of internal control at PT XYZ, a company engaged in construction and IoT-based technology. The research employed a quantitative approach with an explanatory design. Data were collected from all 88 employees involved in the financial reporting process using a structured questionnaire. The analysis was conducted with Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS 4.0. The results show that HR significantly influences both internal control and the quality of financial reports, while AIS significantly affects internal control and financial report quality. Internal control itself positively and significantly impacts financial report quality. Furthermore, internal control was found to mediate the relationship between HR and financial report quality as well as between AIS and financial report quality. These findings highlight the importance of competent HR, reliable AIS, and effective internal control in ensuring the quality of financial reports. This study contributes to the literature by clarifying mixed empirical evidence from previous research and offers practical implications for companies to strengthen internal control systems and human capital development to enhance financial reporting quality.